Effect of bars on the galaxy properties - Vera Rueda, Gustavo Matías (2016)
Aims. With the aim of assessing the effects of bars on disk galaxy properties, we present an analysis of different characteristics of spiral galaxies with strong bars, weak bars and without bars. Methods. We identified barred galaxies from the Sloan Digital Sky Survey (SDSS). By visual inspection of SDSS images we classified the face-on spiral galaxies brighter than g< 16.5 mag into strong-bar, weak-bar, and unbarred galaxies. With the goal of providing an appropriate quantification of the influence of bars on galaxy properties, we also constructed a suitable control sample of unbarred galaxies with similar redshifts, magnitudes, morphology, bulge sizes, and local density environment distributions to those of barred galaxies. Results. We found 522 strong-barred and 770 weak-barred galaxies; this represents a bar fraction of 25.82% with respect to the full sample of spiral galaxies, in good agreement with several previous studies. We also found that strong-barred galaxies show lower efficiency in star formation activity and older stellar populations (as derived with the Dn(4000) spectral index) with respect to weak-barred and unbarred spirals from the control sample. In addition, there is a significant excess of strong-barred galaxies with red colors. The color-color and color-magnitude diagrams show that unbarred and weak-barred galaxies are more extended towards the blue zone, while strong-barred disk objects are mostly grouped in the red region. Strong-barred galaxies present an important excess of high metallicity values compared to unbarred and weak-barred disk objects, which show similar distributions. Regarding the mass-metallicity relation, we found that weak-barred and unbarred galaxies are fitted by similar curves, while strong-barred ones show a curve that falls abruptly with more significance in the range of low stellar masses (log (M-/M⊙) < 10.0). These results would indicate that prominent bars produced an accelerating effect on the gas processing, reflected in the significant changes in the physical properties of the host galaxies.